Implementation of Character Education Management in Coaching Students' Morals - Nuraeni, Nuraeni (Universitas Negeri Malang, 2024)
Abstract: The purpose of this research is to determine the concept of planning, implementing, organizing, as well as monitoring and evaluating character education management in developing students' morals at MA Subulussalam Kresek Tangerang. This research method uses qualitative methods. This type of research uses a phenomenological approach. The subjects of this research were school principals, curriculum areas, teachers of moral beliefs, as well as observations made by researchers. There are several data collection techniques, namely observation, interviews, and document study. There are two research instruments chosen by researchers, namely observation and interviews. In this research, observation and interview techniques were used to obtain data regarding how character education management is implemented in developing students' morals at MA Subulussalam Kresek Tangerang. This research found 1) that at MA Subulussalam Tangerang, in managing student character education management planning, it involved all elements including the school, stakeholders (district head, police chief, village head and religious leaders) and the community 2) In organizing character education management in coaching The morals carried out by MA Subulussalam Kresek Tangerang are through coordination between the school and the government and the community, in this case the parents/guardians of the students. 3) Implementation of character education management involves all elements of the school, including principals, teachers, school guards and canteen attendants, who play a role in creating conducive conditions for the development of students' character. 4) Controlling character education management takes the form of observation by creating assessment rubrics and Learning Implementation Plans.Keywords: Planning, Management, Education, Character, Morals